Richard Z. Johnson, The Revised Statutes of Idaho Territory: Enacted at the Fourteenth Session of the Legislative Assembly: In Force June 1, 1887 Page 729, § 6706 - (:unkn) unknown (General Publisher, 1887)
Enhanced the sentence of any person who assaults, beats another with a cowhide, stick, or whip and, having in his possession, a pistol or other deadly weapon with intent to intimidate or prevent the person assaulted from defending himself. Offenders punished by imprisonment in territorial prison not less than one nor more than four years.
--
Keywords: CARRY - INTENT TO COMMIT CRIME